A system architecture based on open source enterprise content management systems for supporting educational institutions. Issue 2 (April 2016) - Maican, Catalin; Lixandroiu, Radu
Highlights: Higher education institutions as enterprises, regarded mainly from administrative point of view. Enterprise Content Management in the context of administration in academic institutions. Records management, business process management, digital asset management and e-portfolios as main components of ECM (multiple points of view). Framework comprising ECM components and University Management System for students/teachers/researchers and administration. Implementation details with emphasis document workflow in a large Romanian University. Abstract: As academic institutions produce large amounts of information in their teaching/research and administrative activities and this information should flow smoothly between departments, there appears the need to organize and manage this information thoroughly. In order to avoid information overlapping, this should happen considering the other internal existing systems. Nevertheless, because not all institutions afford to spend a lot on various systems, open source software is an appropriate solution for both educational and administrative services. Our aim is to prove the utility of Enterprise Content Management (ECM) in context of academic organizations. The first part makes an introduction to the concepts of ECM and open source software, as means to enhance process management. The second part regards the components of ECM systems and makes an analysis of their potential use in academic institutions. A system architecture based on ECM, by means of which ECM is usefully connected to other systems operating in educational establishments is proposed. A case study, discussing the implementation of an open source ECM in a large Romanian university, showing its efficacy and focusing on features related to document workflow, is analyzed.